Nationally automated colonoscopy performance feedback increases polyp detection: the NED APRIQOT randomized controlled trial - Catlow, Jamie; Sharp, Linda; Wagnild, Janelle; Lu, Liya; Bhardwaj-Gosling, Rashmi; Ogundimu, Emmanuel; Kasim, Adetayo; Brookes, Matthew; Lee, Thomas; McCarthy, Stephen; Gray, Joanne; Sniehotta, Falko F.; et al. (Clinical gastroenterology and hepatology, 2024)
Background & Aims - Postcolonoscopy colorectal cancer incidence and mortality rates are higher for endoscopists with low polyp detection rates. Using the UK’s National Endoscopy Database (NED), which automatically captures real-time data, we assessed if providing feedback of case-mix-adjusted mean number of polyps (aMNP), as a key performance indicator, improved endoscopists’ performance. Feedback was delivered via a theory-informed, evidence-based audit and feedback intervention. - Methods - This multicenter, prospective, NED Automated Performance Reports to Improve Quality Outcomes Trial randomized National Health Service endoscopy centers to intervention or control. Intervention-arm endoscopists were e-mailed tailored monthly reports automatically generated within NED, informed by qualitative interviews and behavior change theory. The primary outcome was endoscopists’ aMNP during the 9-month intervention. - Results - From November 2020 to July 2021, 541 endoscopists across 36 centers (19 intervention; 17 control) performed 54,770 procedures during the intervention, and 15,960 procedures during the 3-month postintervention period. Comparing the intervention arm with the control arm, endoscopists during the intervention period: aMNP was nonsignificantly higher (7%; 95% CI, -1% to 14%; P = .08). The unadjusted MNP (10%; 95% CI, 1%-20%) and polyp detection rate (10%; 95% CI, 4%-16%) were significantly higher. Differences were not maintained in the postintervention period. In the intervention arm, endoscopists accessing NED Automated Performance Reports to Improve Quality Outcomes Trial webpages had a higher aMNP than those who did not (aMNP, 118 vs 102; P = .03). - Conclusions - Although our automated feedback intervention did not increase aMNP significantly in the intervention period, MNP and polyp detection rate did improve significantly. Engaged endoscopists benefited most and improvements were not maintained postintervention; future work should address engagement in feedback and consider the effectiveness of continuous feedback. Clinical trials registry: www.isrctn.org ISRCTN11126923 .
Online verfügbar: 16. Mai 2024, Artikelversion: 21. August 2024
Gesehen am 07.11.2024